Mining in big data and its impact on decision-making from the point of view of managers and heads of departments of administrative units in the Ministry of Health in the Kingdom of Saudi Arabia - Alqahtani, Abdullah Ali Saeed (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the views of managers and heads of departments of administrative units in the Ministry of Health towards the impact of big data mining and decision-making. It also aimed to determine the statistical differences in the answers of department heads managers and the extent to which they are affected by their personal and job characteristics. The study population consisted of directors and heads of departments at the Ministry of Health, and a random sample of (168) individuals was selected. The study concluded the following: The four elements of big data mining that were identified in the current study have a significant impact on decision-making, and the most influential elements were the importance of big data mining, the requirements for the use of big data mining, the areas of use of big data mining. The study showed that there were no statistically significant differences in the impact of big data mining on decision-making according to personal and functional variables for the majority of the study sample, including managers and heads of departments of administrative units. The study recommended the necessity of providing adequate training opportunities to keep pace with the rapid development in relying on big data mining in making decisions. Spreading the concept of big data mining among managers and heads of departments. That it be a priority for the Ministry of Health to develop a full strategic vision for the application and use of big data mining and to benefit from previous experiences in international organizations and institutions.
Keywords: Big Data; Making Decisions; Technological Advances; Managers; Heads of administrative units; Health Sector